Influence of synthesis factors on properties of geopolymers based on red mud and rice husk ash - Tuyen, Tran Ngoc; Quyen, Nguyen Duc Vu; Hai, Ho Van Minh; Tin, Dang Xuan; Quang, Tran Ngoc (Vietnam Journal of Science and Technology, 2017)
In this paper, the effect of mixing ratio of raw materials, curing temperature and time on geopolymerization between red mud and rice husk ash were investigated. The results showed that the optimum conditions were SiO2/Al2O3 ratio of 4 and Na2O/Al2O3 ratio of 2.0, curing temperature of 100oC and curing time of 24 hours. The compressive strength, bulk density, total shrinkage of the obtained product were 22.8 MPa, 2.39 g.cm-3, 15%, respectively that met requirement of unsintered bricks using for construction.